Polyphenolic Acetylcholinesterase Inhibitors from Hopea chinensis - Yan, Tong; Wang, Ting; Wei, Wei; Jiang, Nan; Qin, Yan Hua; Tan, Ren Xiang; Ge, Hui Ming (Planta Medica, 2012)
Bioassay-guided investigation of the stem bark of Hopea chinensis led to the isolation of two new polyphenols, hopeachinols C (1) and D (2), together with ten known compounds (3–12). Compounds 1 and 2 were determined by extensive analysis of spectroscopic data and computational methods. All of these phytochemicals were tested for acetylcholinesterase inhibitory activity, and five resveratrol-derived compounds (1 and 7–10) exhibited significant activity with their IC50 values ranging from 4.81 to 11.71 µM.
Keywords: Hopea chinensis Hand.-Mazz.; Dipterocarpaceae; acetylcholinesterase inhibitor; polyphenol; structure elucidation